UNLOCKING INSIGHTS: ASSESSING THE IMPACT OF FINANCIAL INDICATORS THROUGH REGRESSION ANALYSIS - Ruchiyat, Endang; Fitriana; Faisal, Ijang (Journal of Jabar Economic Society Networking Forum, 2024)
This research aims to evaluate the influence of main financial indicators - net profit, debt to equity ratio (DER), revenue, and operational cash flow - on company financial performance as measured by Return on Assets (ROA) and Return on Equity (ROE). Using a multiple linear regression model, data from 50 companies listed on the Indonesia Stock Exchange (BEI) during the 2015-2020 period was analyzed to identify the relationship between these independent variables and financial performance. The research results show that net profit, revenue and operational cash flow have a significant positive influence on the company's financial performance, while DER has a significant negative influence. The Adjusted R² values for the ROA and ROE models are 0.642 and 0.613 respectively, indicating that this model is able to explain around 64.2% and 61.3% of the variation in the company's financial performance. The F-Statistic which is significant at the 1% level indicates that the independent variables together have a significant effect on financial performance. These findings emphasize the importance of effective management of net profit, revenue and operational cash flow in an effort to improve the company's financial performance. On the other hand, companies need to be careful in using debt to maintain financial stability. Based on these results, companies are advised to improve operational efficiency, marketing strategies and cash flow management, as well as control the use of debt to maximize financial performance. Further research is recommended to consider the influence of external factors and other variables not included in this model, in order to gain a more comprehensive understanding of the factors that influence a company's financial performance.